2018
DOI: 10.4103/ijmr.ijmr_524_18
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress as a possible pathogenic cofactor of post-menopausal osteoporosis

Abstract: Post-menopausal osteoporosis (PO) is one of the major health issues associated with menopause-related oestrogen withdrawal. Despite the intense research and the relevant progress achieved in the last two decades, the pathogenic mechanism underlying PO is still poorly understood. As a consequence of this gap in the knowledge, such disorder and the related complications are still difficult to be effectively prevented. A wealth of experimental and epidemiological/clinical evidence suggests that the endocrine chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…ERα knockout female mice are known to display increased fat pad masses and adipocyte size ( Heine et al, 2000 ), and we previously demonstrated that ERα is required for fat loss by 17α-E2 in intact male mice ( Mann et al, 2020 ). This suggests that 17α-E2 may beneficially modulate adiposity in OVX females through ERα-mediated mechanisms, which could potentially be related to estrogenic upregulation of antioxidant enzymes and suppression of mitochondrial reactive oxygen species production ( Borras et al, 2010 ; Bonaccorsi et al, 2018 ; Yang et al, 2014 ). Although we did not directly evaluate oxidative stress or systemic metabolic parameters in this study, we surmise that longer term studies including a battery of mitochondrial assessments and/or metabolic-related outcomes would prove fruitful in determining if 17α-E2 can mitigate OVX-related metabolic declines similarly to the observed adiposity reductions.…”
Section: Discussionmentioning
confidence: 99%
“…ERα knockout female mice are known to display increased fat pad masses and adipocyte size ( Heine et al, 2000 ), and we previously demonstrated that ERα is required for fat loss by 17α-E2 in intact male mice ( Mann et al, 2020 ). This suggests that 17α-E2 may beneficially modulate adiposity in OVX females through ERα-mediated mechanisms, which could potentially be related to estrogenic upregulation of antioxidant enzymes and suppression of mitochondrial reactive oxygen species production ( Borras et al, 2010 ; Bonaccorsi et al, 2018 ; Yang et al, 2014 ). Although we did not directly evaluate oxidative stress or systemic metabolic parameters in this study, we surmise that longer term studies including a battery of mitochondrial assessments and/or metabolic-related outcomes would prove fruitful in determining if 17α-E2 can mitigate OVX-related metabolic declines similarly to the observed adiposity reductions.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in accordance with many previous studies that reported the anti-oxidant activity of L. sativum [ 19 , 31 , 32 , 33 ]. There is ample evidence linking oxidative stress to the development of post-menopausal osteoporosis [ 34 , 35 ]. Bone resorption has been shown to occur due to the disturbance in mineral tissue homeostasis resulting from increased reactive oxygen species (ROSs) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…MK-7 supplementation increased gap closure and increased proliferation compared to osteogenic medium alone. It is widely accepted that oxidative stress accelerates the rate of bone loss and is one of the risk and pathogenic factors in osteoporosis (Sánchez-Rodríguez et al, 2007 ; Manolagas and Parfitt, 2010 ; Bonaccorsi et al, 2018 ). Our group has previously noted increases in production of ROS species to be associated with ectopic vascular calcification in vitro (Furmanik et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%